2019
DOI: 10.1002/osp4.385
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and cognitive function among adults with excess adiposity

Abstract: Summary Background Adverse childhood experiences (ACEs) and obesity are independently associated with brain/neurocognitive health. Despite a growing emphasis on the importance of early life adversity on health, the relationship between ACEs and neurocognition in adults with overweight/obesity is unclear. The objective was to examine associations between self‐reported ACEs and measured neurocognitive domains in a sample of adults with overweight/obesity. Methods Participants were 95 predominantly white, highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Previous work suggested that higher ACEs were linked to higher BMIs and greater abdominal adiposity in a treatment-seeking sample of adults with overweight/obesity. 45 The present study expands these results by examining the associations between a history of selfreported ACEs and weight cycling. It is hypothesized that persons with higher ACE scores would be more likely to endorse a history of weight cycling.…”
Section: Introductionmentioning
confidence: 67%
“…Previous work suggested that higher ACEs were linked to higher BMIs and greater abdominal adiposity in a treatment-seeking sample of adults with overweight/obesity. 45 The present study expands these results by examining the associations between a history of selfreported ACEs and weight cycling. It is hypothesized that persons with higher ACE scores would be more likely to endorse a history of weight cycling.…”
Section: Introductionmentioning
confidence: 67%
“…In the exploration of this relationship, some research focused on war trauma ( Wittekind et al, 2016 ; Fohn et al, 2017 ; Peltonen et al, 2017 ; Wittekind et al, 2017 ), on natural catastrophes ( Weems et al, 2014 ; Dawson and Bryant, 2016 ; Tian et al, 2018 ), on terroristic attacks ( Vallet et al, 2017 ), on accidents ( Hitchcock et al, 2014b ; McKinnon et al, 2017 ), and on stressful medical care ( McKinnon et al, 2017 ; Risløv Staugaard et al, 2017 ; Goldfarb et al, 2019 ), while others on interpersonal trauma such as neglect, sexual abuse, maltreatment, parental separation, parental bereaved or overprotection ( Crane et al, 2014 ; Huntjens et al, 2014 ; Neshat Doost et al, 2014 ; Berthelot et al, 2015 ; Kaynar and Er, 2015 ; Griffith et al, 2016 ; Harris et al, 2016 ; Varnaseri et al, 2016 ; Wang et al, 2016 ; McCrory et al, 2017 ; Kaczmarczyk et al, 2018 ; Hawkins et al, 2020 ; Jiang et al, 2020 ; Barry et al, 2021 ; Bendstrup et al, 2021 ; Ding and He, 2021 ; Hakamata et al, 2021 ; Lawson et al, 2021 ; Salomão et al, 2021 ; Alaftar and Uzer, 2022 ; Chiasson et al, 2022 ; D’Amico et al, 2022 ; Lin et al, 2022 ; Thomson and Jaque, 2022 ; Wolf and Nochajski, 2022 ; Zhu and Hakim-Larson, 2022 ; Fishere and Habermas, 2023 ; Goldfarb et al, 2023 ; Zhang et al, 2023 ). Other studies assessed both non-interpersonal and interpersonal trauma within the same sample ( Parlar et al, 2016 ; Saleh et al, 2017 ; Feurer et al, 2018 ; Staniloiu et al, 2018 ; Viard et al, 2019 ; Pacheco and Scheeringa, 2022 ;…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our first hypothesis, a greater frequency of ACEs was significantly associated with the severity of an individual’s cardiometabolic dysregulation. The alterations on the structure and function of biological and neuroendocrine systems as a consequence of frequent or severe ACEs have been postulated to be the result of dysfunctional glucocorticoid receptor stimulation (4). Specifically, as a normal consequence of stress, the glucocorticoid receptor signaling pathway stimulates the production of multiple cardiometabolic biomarkers such as glucose, triglycerides, and elevated blood pressure (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…The injurious effects of ACEs begin to arise when children are exposed to prolonged or frequent distressing events, such as emotional, physical, and/or sexual abuse, neglect, financial strain, loss of a parent, and/or household dysfunction in the form of parental divorce or household substance abuse (2). Research shows that ACEs can lead to the development of a toxic stress response, which in turn can affect an individual’s physiology at a cellular level (3), resulting in chronic cognitive impairments in later life, specifically in the domains of fluid cognition and episodic memory (4). However, relatively little research has examined potential biological pathways linking ACEs and cognition in adults.…”
Section: Introductionmentioning
confidence: 99%